Feeding the brain: the importance of nutrients for brain functions and health - Altomare, Roberta; Damiano, Giuseppe; Palumbo, Vincenzo Davide; Buscemi, Salvatore; Spinelli, Gabriele; Cacciabaudo, Francesco; Lo Monte, Giulia; Maffongelli, Angela; Fazzotta, Salvatore; Gulotta, Eliana; Gulotta, Leonardo; Altomare, Silvia; et al. (Progress in Nutrition, 2017)
‘We are what we eat’, said the philosopher Feuerbach. In fact, the quality of the food we eat affects our mind as well: the brain, which represents 2% of our body weight, consumes about 20% of the calories we eat each day. Follow a few rules could therefore help to feed properly our brain, so it works to the best of its ability. It is important to know properties of foods especially regarding their aminoacidic composition because aminoacids are components of neurotransmitters, molecules needed for brain transmission and function. It is also possible to choose specific food to prevent or support different diseases that affects nervous system.